Unraveling the Causal Links Between Immune Traits and Hepatocellular Carcinoma: Insights From a Bi-Directional Mendelian Randomization Study - Li, Jie; Wang, Gechun; Xiang, Xiaonan; Wang, Jianguo (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Hepatocellular carcinoma (HCC) is significantly influenced by the immune system, which plays a key role in its devel opment, progression, treatment, and prognosis. While observational studies have revealed correlations between circulating immune traits and HCC, their genetic basis and causal links remain unclear. This study aims to investigate the genetic associations and bidirec tional causal relationships between immune traits and HCC risk using Mendelian randomization (MR) approaches. Materials and Methods: Genome-wide association study summary statistics from the FinnGen cohort (R9, including 453 HCC cases and 287 137 controls) were used to perform a bidirectional two-sample MR analysis. The causal effects of immune traits on HCC, as well as reverse causality, were assessed. Sensitivity analyses, including heterogeneity and pleiotropy tests, were used to ensure the robustness and validity of the results. Results: Thirty-nine immune traits were identified to be significantly associated with HCC risk. Elevated levels of 10 immune traits were positively associated with increased HCC risk, while the abundance of 29 immune traits was inversely correlated with HCC incidence. Furthermore, the reverse MR analysis revealed significant causal effects of HCC on 11 immune traits. Conclusion: This study provides strong evidence of genetic links between systematic immune cell profiles and HCC, shedding light on the mechanisms underlying its onset and progression. These findings identify potential immune biomarkers for early diagnosis and immune-targeted therapies. Cite this article as: Li J, Wang G, Xiang X, Wang J. Unraveling the causal links between immune traits and hepatocellular carcinoma: Insights from a bi-directional mendelian randomization study. Turk J Gastroenterol. 2025;36(7):420-430.